COVID self-certification: recognition of postgraduate training and experiences gained during the pandemic. (2021) - Ehilawa, Patience; Thompson, Fiona; Muldoon, Sarah; Ahmed, Rana; Ariyo, Mary; Corne, Jonathan; Sadler, Paul
No abstract available